Szanse rozwoju agroturystyki w województwie zachodniopomorskim w kontekście integracji z UE - Malkowski, Arkadiusz (The Chances of Agri-Tourism Development in West-Pomeranian Voivodship in Context of Integration with EU, 2005)
Agri-tourism is considered by farmers one of the most important ways to the diversification of income sources. The development of this type of tourism is an important chance of stimulating rural economy. The integration with EU is the chance on development of agri-tourism in border regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 61-66